The seven wonders of the modern world - Cox, Reg.; Morris, Neil. (Philadelphia, Pa. : Chelsea House Pub., 2001)
Describes in detail the design and construction of seven modern feats of architecture and engineering: the Sydney Opera House, Channel Tunnel, Kansai Airport, the Concorde, Aswan High Dam, Sears Tower, and Kennedy Space Center.
"First published in the UK in 1996 by Belitha Press Limited..."--Colophon.
Includes index.
6.6
5-8.
5-8
Keywords: Architecture -- Juvenile literature; Engineering -- Juvenile literature; Seven Wonders of the World -- Juvenile literature; Architecture; Engineering; Seven Wonders of the World; Architecture; Curiosities and wonders; Engineering